Anion Exchange Ionomers: Impact of Chemistry on Thin‐Film Properties. (9th March 2021) - Luo, Xiaoyan; Kushner, Douglas I.; Li, Jonathan; Park, Eun Joo; Kim, Yu Seung; Kusoglu, Ahmet
Abstract: Ionomer thin‐films (i.e., 20–100 nm) on supports serve as model systems to understand ionomer‐catalyst interfacial behavior as well as the confinement‐driven deviation in properties from bulk membranes. While ionomer thin‐films have been examined for proton exchange ionomers, the thin‐film properties of anion exchange ionomers (AEIs) remain largely unexplored. More importantly, delineating the convoluted impact of chemistry and confinement on thin‐film morphology and hydration is of interest to advancing the field on functional ionic interfaces. In this work, these aspects are studied by using AEIs of different backbones (perfluorinated, aliphatic, and aromatic) and side chains (various lengths, and single versus dual functional groups). Quartz‐crystal microbalance and spectroscopic ellipsometry are used to analyze density and coupled with calculated free volume fraction of thin‐films to provide insights on their gas transport properties. AEI side‐chain's chemical character plays a key role in how confinement modulates hydration (in thin‐film versus bulk). The results elucidate the effects of backbone, side‐chain chemistry versus anion/cation type in the confinement‐driven changes in thin‐film morphology and swelling. This study also provides new insights for tuning AEI transport functionalities at interfaces via chemistry, which can benefit the design and development of electrode‐ionomers for alkaline membrane‐based energy systems. Abstract : The results underscore the role of chemistry in tuning the transport (i.e., water, ion, and gas) functionalities of anion exchange ionomer thin‐films and the confinement‐anion interplay, and therefore provide guidance for the design of next‐generation ionomers for the electrodes of alkaline fuel cells, water, and CO2 electrolyzers, and other electrochemical systems, wherein thin‐films provide critical transport functionalities.